Pemberdayaan Wanita Usia Subur Dalam Deteksi Dini Kanker Cerviks Melalui Pemeriksaan IVA - Nella Vallen Ika Puspita; Anis Ardiyanti; Rinda Intan Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Cervical cancer is a disease that can be detected early in various ways, one of which is screening. Based on its effectiveness, detection that can be done is by means of pap smears and IVA tests. The IVA test is an initial action to detect changes in abnormal cervical cells and can be carried out in all types of health services, including community health centers. Here partners are not yet motivated to carry out screening. So it is necessary to provide education about early detection screening for cervical cancer.